EFFECT OF USING GEOPOLYMER MORTAR IN FERROCEMENT BY VARYING THE COMBINATION, NUMBER AND SIZES OF MESHES - Borude R. V.; Prof. Pandit R.D (International Journal of Innovations in Engineering Research and Technology, 2021)
Globally, Cement production contributes about 1.6 billion tons of CO2 or about 7% of global loading of CO2 into the atmosphere. The manufacture of Cement Releases Carbon dioxide that is significant contributor of Green house gas emissions to the atmosphere. So there was a need to develope and use eco-friendly material having similar properties as like of cement mortar. Geopolymer is produced without the presence of cement as a binder; instead, the base material such as fly ash, that is rich in Silicon (Si) and Aluminium (Al), is activated by alkaline solution to produce the binder. Hence Geopolymer mortar can be used instead of cement mortar which will have no adverse effect on our environment. Ferrocement is a composite material formed by closely spaced wire mesh which uses wire meshes as reinforcement and filled with rich cement mortar. Experimental investigation was carried out to study the effect of Geopolymer mortar in Ferrocement for variation in mesh size and number of layers. For this, tensile testing was done on Geo-ferrocement specimens of size 750 x 60 x 30 mm reinforced with single, double, triple layer using variation in meshes of different sizes. Similarly, compression testing of cubical specimens of side 70 mm reinforced with single, double, triple layer of meshes sizes was done. Results indicated an significant increase in tensile strength and compressive strength of specimens with increase in number of layer of meshes. Test results also provided the most suitable combination and size of mesh to be used for obtaining the maximum strength of different sizes was done.